Models of maternity care: a continuity of midwifery care - Choudhary, Suman; Jelly, Prasuna; Mahala, Prakash (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Pregnancy and birth are significant life events for women and their families and midwife supports a woman throughout pregnancy, birth and the postnatal period. So, the demand for services that are family friendly, women focused, safe and accessible is increasing. Evidence has shown that midwifery care is associated with lower cost, higher satisfaction rates among women, and less intervention. Because pregnancy and childbirth involve every part of feelings, physical and practical needs, hopes, religious and spiritual beliefs can all affect pregnancy and birth. So, model of maternity care addresses all these aspects to help give birth safely, naturally and confidently. The aim of this review is how midwives working in different model care constructed their midwifery role in order to maintain a positive work-life balance. Evidence from high income countries found such models to be a cost-efficient way to improve health outcomes, reducing medical interventions and increasing satisfaction with care.